Pembuatan Biodiesel Dari Minyak Biji Kapuk (Ceiba Pentandra) Dengan Katalis Lempung Teraktivasi; Pengaruh Kecepatan Pengadukan - Putri, Erlisa Yanuari; Bahri, Syaiful; Saputra, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Biodiesel producted by transesterifiation reaction which on energy source. Biodiesel was developed in Indonesia as an anticipatis of energy crisis problem suppported by goverment national energy policy. This research is aimed to make biodiesel from cotton seed oil, studying the effect of agitation speed to the amount of biodiesel produced and determined the best catalyst activated by acid or base, and determined the characteristics of biodiesel produced. The transesterification process was occured at a temperature of 60oC, on weight of oil 100 grams, reaction time 1,5 hours, mole ratio of oil to methanol 1 : 9, catalyst concentration 0,5% -weight of oil for varions of agitation rate 400, 500 and 600 rpm, and variations of catalyst acid 0,47, 0,62 and 0,78% and alkaline activated with a concentration of 0,33, 0,44 and 0,66%. From the result was obtained the highest biodiesel yield of 95,45% for alkaline activated 0,66% for agitation speed of 400 rpm. Characterization of physical properties of biodiesel obtained here density of 878 kg/m3, 3,03 mm2/s kinematic viscosity, acid number 0.34 mg KOH/g sample, and the flash point 195oC.Keywords: biodiesel, clay catalysts, activation of acids and bases, transesterification